Inhibition pattern of sulfamide-related compounds in binding to carbonic anhydrase isoforms I, II, VII, XII and XIV - Gavernet, Luciana (2013)
A set of sulfamides and sulfamates were synthesized and tested against several isoforms of carbonic anhydrase: CA I, CA II, CA VII, CA XII and CA XIV. The biological assays showed a broad range of inhibitory activity, and interesting results were found for several compounds in terms of activity (Ki <1 μm) and selectivity: some aromatic sulfamides are active against CA I, CA II and/or CA VII; while they are less active in CA XII and CA XIV. On the other hand, bulky sulfamides are selective to CA VII. To understand the origin of the different inhibitory activity against each isozyme we used molecular modeling techniques such as docking and molecular dynamic simulations.